2013
DOI: 10.1021/bi401080k
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of Lipid-Free Human Apolipoprotein A-I in Solution

Abstract: Apolipoprotein AI (apoA-I) is the principal acceptor of lipids from ATP-binding cassette transporter A1, a process that yields nascent high density lipoproteins. Analysis of lipidated apoA-I conformation yields a belt or twisted belt in which two strands of apoA-I lie antiparallel to one another. In contrast, biophysical studies have suggested that a part of lipid-free apoA-I was arranged in a 4-helix bundle. To understand how lipid-free apoA-I opens from a bundle to a belt while accepting lipid it was necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 78 publications
10
66
0
1
Order By: Relevance
“…The secondary structure assignment for residues in the proposed conformation ( Fig. 2B ) is close to that found in hydrogen exchange and mass spectrometry studies ( 40 ), and the tertiary conformation is similar to the four-helical bundle core region of apoA-I inferred from cross-linking studies ( 41,42 ). These observations, together with recent studies that explain conformational and functional features of apoA-I and its natural variants based on the crystal structure and the proposed lipid-free conformation ( 43,44 ), support the view that the proposed conformation for the lipid-free its clearance from the circulation ( 14,21,22 ) and also affect various reverse cholesterol transport pathways that directly modulate plasma HDL cholesterol and apoA-I levels, such as LCAT activation, ABCA-1 mediated effl ux of cholesterol, or the interaction with scavenger receptor class B type I ( 9-11, 15, 16, 50, 51 ), while enhanced binding of the mutated apoA-I to TG-rich lipoproteins may be one of the mechanisms contributing to HTG.…”
Section: Ans Fl Uorescencesupporting
confidence: 78%
“…The secondary structure assignment for residues in the proposed conformation ( Fig. 2B ) is close to that found in hydrogen exchange and mass spectrometry studies ( 40 ), and the tertiary conformation is similar to the four-helical bundle core region of apoA-I inferred from cross-linking studies ( 41,42 ). These observations, together with recent studies that explain conformational and functional features of apoA-I and its natural variants based on the crystal structure and the proposed lipid-free conformation ( 43,44 ), support the view that the proposed conformation for the lipid-free its clearance from the circulation ( 14,21,22 ) and also affect various reverse cholesterol transport pathways that directly modulate plasma HDL cholesterol and apoA-I levels, such as LCAT activation, ABCA-1 mediated effl ux of cholesterol, or the interaction with scavenger receptor class B type I ( 9-11, 15, 16, 50, 51 ), while enhanced binding of the mutated apoA-I to TG-rich lipoproteins may be one of the mechanisms contributing to HTG.…”
Section: Ans Fl Uorescencesupporting
confidence: 78%
“…The HX-derived secondary structure for lipid-free apoA-I suggested that the whole C-terminal domain lacks defined structure (12). In addition, lipid-free apoA-I models based on cross-linking experiments suggested that part of the H10 region formed helical structure (37,38). Most recently, MD simulation of full-length apoA-I based on Borhani et al's (35) and our crystal structure suggested that parts of H8 and H10 form helical structure after equilibrium in solution (30).…”
mentioning
confidence: 99%
“…Finally, we acknowledge the strong experimental evidence showing that apoA-I exhibits molten globule characteristics in solution (29,30,35,45). apoA-I has a free energy of denaturation that is well below that of most soluble proteins (45,46) with helical segments that are constantly folding and unfolding on a time scale of seconds (44).…”
Section: Discussionmentioning
confidence: 94%